Mother's Knowledge and Role in Stimulating Child Development in Posyandu RW 07 Citarip Village Bandung City - Liliek Fauziah (Healthy-Mu Journal, 2023)
Stimulation is an activity carried out to stimulate children's basic abilities so that they can grow and develop optimally. One of the right stimulations for children is to stimulate the child's thinking power to utilize their emotional, social and physical aspects by playing. The research method used is descriptive quantitative with cross sectional design. The population in this research is 65 people with total sampling technique. The instrument used is a questionnaire consisting of knowledge and the role of the mother regarding the stimulation of child development. The research location is in RW07 Citarip village, Bandung City. The univariate analysis used is the frequency distribution. The results in the study were that some of the respondents (63.08%) mothers who had children under five in RW 07 Citarip had good knowledge regarding stimulation of child development. almost half of the respondents (70.77%) mothers who have children under five in RW 07 Citarip have a good role regarding child development. Recommendations in this study It is hoped that mothers can provide stimulation, detection and intervention as early as possible on child development that can be done at Posyandu.